Join the growing community of curious minds on IDNLearn.com and get the answers you need. Ask your questions and receive reliable and comprehensive answers from our dedicated community of professionals.
Sagot :
To solve the equation [tex]\(6x + c = k\)[/tex] for [tex]\(x\)[/tex], follow these steps:
1. Start with the given equation:
[tex]\[ 6x + c = k \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]. To do this, subtract [tex]\(c\)[/tex] from both sides of the equation:
[tex]\[ 6x + c - c = k - c \][/tex]
Simplifying gives:
[tex]\[ 6x = k - c \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides of the equation by 6:
[tex]\[ x = \frac{k - c}{6} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(k\)[/tex] and [tex]\(c\)[/tex] is:
[tex]\[ x = \frac{k - c}{6} \][/tex]
Therefore, the correct answer is:
C. [tex]\( x = \frac{k - c}{6} \)[/tex]
1. Start with the given equation:
[tex]\[ 6x + c = k \][/tex]
2. Isolate the term involving [tex]\(x\)[/tex]. To do this, subtract [tex]\(c\)[/tex] from both sides of the equation:
[tex]\[ 6x + c - c = k - c \][/tex]
Simplifying gives:
[tex]\[ 6x = k - c \][/tex]
3. Solve for [tex]\(x\)[/tex] by dividing both sides of the equation by 6:
[tex]\[ x = \frac{k - c}{6} \][/tex]
Thus, the solution for [tex]\(x\)[/tex] in terms of [tex]\(k\)[/tex] and [tex]\(c\)[/tex] is:
[tex]\[ x = \frac{k - c}{6} \][/tex]
Therefore, the correct answer is:
C. [tex]\( x = \frac{k - c}{6} \)[/tex]
Thank you for contributing to our discussion. Don't forget to check back for new answers. Keep asking, answering, and sharing useful information. IDNLearn.com has the solutions you’re looking for. Thanks for visiting, and see you next time for more reliable information.